Portal Vein Embolization with PVA and Coils before Major Hepatectomy: Single-Center Retrospective Analysis in Sixty-Four Patients. (10th October 2019) - Camelo, R.; Luz, J. H.; Gomes, F. V.; Coimbra, E.; Costa, N. V.; Bilhim, T.
Abstract : Objectives . Portal vein embolization (PVE) stimulates hypertrophy of the future liver remnant (FLR) and improves the safety of extended hepatectomy. This study evaluated the efficacy of PVE, performed with PVA and coils, in relation to its effect on FLR volume and ratio. Secondary endpoints were the assessment of PVE complications, accomplishment of liver surgery, and patient outcome after hepatectomy. Materials and Methods . All patients who underwent PVE before planned major hepatectomy between 2013 and 2017 were retrospectively analyzed, comprising a total of 64 patients. Baseline patient clinical characteristics, imaging records, liver volumetric changes, complications, and outcomes were analyzed. Results . There were 45 men and 19 women with a mean age of 64 years. Colorectal liver metastasis was the most frequent liver tumor. The majority of patients ( n = 53) had a right PVE. FLR increased from a mean value of 484 ml ± 242 to 654 ml ± 287p < 0.001 after PVE. Two major complications were experienced after PVE: 1 case of left hepatic artery branch laceration and 1 case of hemoperitoneum and hemothorax. A total of 44 (69%) patients underwent liver surgery. Twenty-one patients were not taken to surgery due to disease progression ( n = 18), liver insufficiency ( n = 1), and insufficient FLR volume ( n = 1), and one patient declined surgery ( n = 1). Conclusions . PVE with PVA and coils was accomplished safely and promoted a high FLR hypertrophy yield, enabling most of our patients to be submitted to the potentially curative treatment of liver tumor resection.